Faktor Yang Mempengaruhi Cash Holding Pada Perusahaan Manufaktur BEI Tahun 2017-2019 - Steven Sean; Vidyarto Nugroho (Fakultas Ekonomi, Universitas Tarumanagara, 2022)
The purpose of this study is to test empirically the effect of company size, profitability, leverage, and liquidity on cash holding in manufacturing companies listed on the Indonesia Stock Exchange for the period 2017 - 2019. This study uses data from 77 manufacturing companies that have been selected using the purposive sampling method. with a total of 231 data for three years. The data used are secondary data in the form of financial reports. This research data processing using the program Eviews version 11 (Econometric Views) for Windows. The results showed that the company size, probability, and leverage were not significant effect on cash holding, liquidity has a significant negative effect on cash holding. The implication of this research is the manager's decision to be the top in the company's decision making how to regulate the cash inflow and outflow policy. Manager's experience is important because with a lot of experience, managers can consider every decision that is right for their company.